Renewable methanol production: Understanding the interplay between storage sizing, renewable mix and dispatchable energy price - Chao Chen; Aidong Yang; René Bañares-Alcántara (Advances in Applied Energy, 2021)
Chemical production using renewable energies is an important element on the roadmap of industry decarbonisation. This work investigates the optimisation of renewable power supply for a fully electrified methanol process, with a focus on the interplay between renewable fix, storage sizing and the use of backup dispatchable power source. The analysis is performed using the meteorological data obtained from two locations, i.e. Kramer Junction (US) and Norderney (Germany), which have excellent solar and wind source, respectively. The minimum levelised energy cost, which is optimised in terms of renewable power generation, renewable mix and storage size, is found to be 106$/MWh and 103$/MWh for operations in Kramer Junction and Norderney, respectively, based on a dispatchable energy price of 230$/MWh. This leads to a levelised methanol cost of 1490$/tonne and 1459$/tonne with a respective renewable penetration of 81% and 96% in the production. The correlation between renewable penetration and dispatchable energy price in the most economical scenario exhibits a two-regime behaviour: the renewable penetration increases dramatically at the beginning and then slowly approaches 100% when the dispatchable energy price is above a critical point. For a fully renewable operation, the optimised levelised energy cost is found to increase to 167$/MWh and 114$/MWh for Kramer Junction and Norderney, respectively. The results show the importance of the dual functionality of hydrogen in the energy storage system, which improves the overall energy efficiency.